Phylogenetic relationships within the Scylla (Portunidae) assessed by the mitochondrial DNA sequence - HURUL ADILA-AIDA MOHAMAD ROSLY; SITI AZIZAH MOHD NOR; DARLINA MD. NAIM (Biodiversitas Journal of Biological Diversity, 2017)
Rosly HAAM, Mohd Nor SA, Md. Naim D. 2017. Phylogenetic relationships within the Scylla (Portunidae) assessed by the mitochondrial DNA sequence. Biodiversitas 18: 1696-1704. This study was centered around the phylogenetic of mud crab genus Scylla collected across Malaysia based on a 542 base pairs (bp) section of the mitochondrial cytochrome c oxidase I (COI) from 201 individuals. Sampling locations were nine areas including one location from Borneo (Sabah and Sarawak). The Maximum Parsimony (MP) and Neighbor-Joining (NJ) methods was conducted for phylogenetic analysis and performed in MEGA ver. 5.05. We found that S. olivacea is the plenteous species collected with 111 individuals, followed by S. tranquebarica with 61 individuals. Scylla paramamosain is barely found throughout our sampling locations with only 29 individuals caught in this study. Regrettably, no wild samples of S. serrata was found during our sampling occasions, accordingly life specimens were purchased from restaurants to complete the analysis. Both MP and NJ phylogenetic trees shows a monophyletic relationships among all four species within genus Scylla included in this study. This was also supported by the genetic distance analysis based on Tamura-Nei which indicates that there is high interspecific and low intraspecific genetic distances among and within species of Scylla included in the analysis. This investigation divulged a solid proof that supports the occurrence of three species of Scylla with the nonappearance of S. serrata in Malaysian waters. This current investigations could serve as a guidance for promoting further assessment on aquaculture and conservation management for the species.